Focus on Innovation Transfer: A Definitional Approach and Derivation of a Theoretical Actor-Process Model and Ten Empirical Success Factors of Transfer - Jakobs, Lasse (Journal of Geography Education, 2021)
In recent years, the transfer of scientific knowledge into educational contexts has become increasingly important. In Geography Didactics, there are major challenges in this regard, which result in multiple transfer deficits. Challenges arise around the concept of transfer and the design of successful transfer processes. This article approaches the concept of transfer in a definition-based way by discussing the directions and tasks of didactic transfer research. Building on a more elaborate understanding, the paper introduces a possible actor-process model of transfer. Based on empirical findings, ten factors of successful transfer processes as well as two best-practice examples complement the model. Finally, the paper addresses implications for transfer research and practice in Geography Didactics.